PENGARUH RISIKO LIKUIDITAS, UKURAN DEWAN KOMISARIS, DAN INDEPENDENSI DEWAN KOMISARIS TERHADAP FEE AUDIT DAN PEMILIHAN AUDITOR INDEPENDEN DI INDONESIA (Studi Empiris pada Perusahaan Properti, Real Estate, dan Konstruksi Bangunan yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020) - Ranisha Putri Pardede; Herry Laksito (Diponegoro Journal of Accounting, 2022)
The aims of this study to analyze and examine the impact of liquidity risk on audit fee and auditor selection, as well as the impact of the characteristics of the board of commissioners on auditor selection in Indonesia. The population that used in this study consists of all property, real estate and building construction companies listed in Indonesian Stock Exchange for the period 2016-2020. Audit fee and auditor selection in this study are the dependent variables and independent variables are liquidity risk, board commissioners size, and board commissioners independence with firm size and ROA as control variables.The sample that used of this study, based on the purposive sampling are 155 samples from 31 companies. The testing of this study using linear regression analysis for audit fee model and logistic regression analysis for auditor selection model. liquidity risk has a significant impact on audit fee, but not on auditor selection in Indonesia's property, real estate and building construction companies. Meanwhile, the characteristics of the board of commissioners, namely board commissioners size and board commissioners independence has no significant impact on auditor selection.